The Use of Chat GPT for Academic Writing in Higher Education - Gultom, Aryadi Manuel; Ashadi, Ashadi; Fatnalaila, Fatnalaila; Azizah, Shofiah Nur; Rosyidah, Dyana Maftuhatu (PT FORMOSA CENDEKIA GLOBAL, 2024)
The integration of artificial intelligence (AI) technology in education has created new opportunities for improving academic writing in higher education. This study investigates the utilization of Chat GPT, an artificial intelligence-powered conversational model, as a tool to assist in writing. Students who used Chat GPT for academic writing were interviewed using a qualitative approach and semi-structured interviews. The data research showed that Chat GPT provides consumers with information regarding its origins, advantages, and trustworthiness. Additionally, it is regarded as a valuable instrument for creating ideas and facilitating the writing process. Nevertheless, the study revealed both benefits and drawbacks associated with its utilization, emphasizing the importance for teachers to maintain a balance between its advantages and potential negatives. The outcomes offer a more profound comprehension of Chat GPT's function in academic writing and propose additional investigation to evaluate its enduring influence on students' writing abilities and rectify any partiality in AI-generated text